Evaluation and mechanism study of Pien Tze Huang against EV-A71 infection - Huiqiang Wang; Fenbei Chen; Shicong Wang; Yuhuan Li; Ting Liu; Yinghong Li; Hongbin Deng; Jingwen Dong; Jing Pang; Danqing Song; Dousheng Zhang; Juan Yu; et al. (Frontiers in Pharmacology, 2023)
Hand, foot, and mouth disease (HFMD) caused by enterovirus A71 (EV-A71) infection, currently lacks specific preventive and therapeutic interventions. Here, we demonstrated that Pien Tze Huang (PZH) could dose-dependently inhibit EV-A71 replication at the cellular level, resulting in significant reductions in EV-A71 virus protein 1 (VP1) expression and viral yields in Vero and human rhabdomyosarcoma cells. More importantly, we confirmed that PZH could protect mice from EV-A71 infection for the first time, with Ribavirin serving as a positive control. PZH treatment reduced EV-A71 VP1 protein expression, viral yields in infected muscles, and improved muscle pathology. Additionally, we conducted a preliminary mechanism study using quantitative proteomics. The results suggested that the suppression of the PI3K/AKT/mTOR and NF-κB signaling pathways may contribute to the anti-EV-A71 activity of PZH. These findings provide strong evidence supporting the potential therapeutic application of PZH for EV-A71 infection management.